Composition and nutritive value of chickpea - Ramalho Ribeiro J.M.C.; Portugal Melo I.M. (Present status and future prospects of chickpea crop production and improvement in the Mediterranean countries, 1990)
The chemical compostion of some samples of chickpea was studied and compared with published values. A critical evaluation of the different nutrients is presented, in particular the aminoacid content. These parameters are analysed in terms of animal requirements and the chickpea has been evaluated as a protein and an energy source of diets for non-ruminant and ruminant animals. The importance and the nutritive value of the chickpea straw is also mentioned.
Present Status and Future Prospects of Chickpea Crop Production and Improvement in the Mediterranean Countries, 11-13 Jul 1988, Zaragoza (Spain)